PERANCANGAN SISTEM PENCETAKAN ONLINE BERBASIS WEB - Gea, Diyurman (Proceedings of KNASTIK, 2010)
Work efficiency and service quality improvement are two important things to compete with other businesses. Hope to keep costs as low with a satisfactory quality of service, can be optimized through the use of technology. By utilizing technology, exchange of data and information can be done easily without any limitation of time and geographical location. One type of business that have the potential to be improved quality of service is a document copying services as implemented in Binus University. In addition to the staff and lecturers, students need the service for various types of documents such as doubling the lecture materials and other administrative documents from softcopy to hardcopy documents. With the number of customers that so many frequent long queues, sometimes the officer / operator overwhelmed and not a few customers who feel disappointed. By leveraging the technology capabilities possessed by a photocopy machine to connect to a network computer, it can be made a system that supports the printing of documents through the Internet, so as to reduce queues and accountable system of administrative procedures. Users can monitor the status of printing the document, whether in a state of waiting, the document is printed or printing the document is complete. Each time the user performs printing, the computer used does not need a printer driver installation process, and the system can be developed to validate the adequacy of the deposit of funds that have been recorded in the database. This paper describes the Online Printing System web-based, and are capable of storing the printing information into a database system, so that records can provide tracking information, which affects the quality of service and performance is excellent.